2011
DOI: 10.1063/1.3651084
|View full text |Cite
|
Sign up to set email alerts
|

Direct solar energy conversion and storage through coupling between photoelectrochemical and ferroelectric effects

Abstract: Harvesting and storing solar energy has become more and more important. Current solid-state photovoltaic cells and conventional photoelectrochemical cells are not capable of directly storing the converted energy, which has to be facilitated by connecting to external storing devices. We demonstrate a device architecture that can convert and store solar energy in the electrical form within an intrinsically single structure. Mobile charge is internally stored, based on the coupling between photoelectrochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Previous work in our group reported that PVDF/Si powder composites could be used as active materials to fabricate a two-electrode DSSC-like photocapacitor, which showed high photoresponse, rechargeability, and long-term storage properties [10]. It implied that the two parts of the PSC can share a single electrolyte, and the dielectric material-functionalized counterelectrode (CE) permits energy storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in our group reported that PVDF/Si powder composites could be used as active materials to fabricate a two-electrode DSSC-like photocapacitor, which showed high photoresponse, rechargeability, and long-term storage properties [10]. It implied that the two parts of the PSC can share a single electrolyte, and the dielectric material-functionalized counterelectrode (CE) permits energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…However, a PVDF/Si photoelectrode can harvest energy, since it generates an open circuit voltage of 0.47 V under solar irradiation. This complicates the role of a PVDF dielectric film for energy storage [10]. In this work, TiO 2 DSSCs with CEs functionalized only by a PVDF dielectric were fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Traditional two-electrode PSCs could not provide continuous power output after being fully charged under steady illumination, since the photogenerated charges are depleted to charge the energy storage section. [8][9][10] In our previous work, a new type of twoelectrode PSC based on dye-sensitized solar cells (DSSCs) was reported with both good photo-to-electric conversion efficiency (g) and energy storage capacity via introducing composited ZnO/polyvinylidene fluoride (PVDF) nanostructure in CE. 12 The polymer/nanostructured oxide system could possess energy storage capability while allowing the passage of carriers through the structure.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Another type of PSCs could be regarded as simplex devices, since they contain only two electrodes: One is for solar energy conversion (photoelectrode) and the other is for energy storage (counter electrode, CE). [8][9][10][11][12][13] Traditional two-electrode PSCs could not provide continuous power output after being fully charged under steady illumination, since the photogenerated charges are depleted to charge the energy storage section. [8][9][10] In our previous work, a new type of twoelectrode PSC based on dye-sensitized solar cells (DSSCs) was reported with both good photo-to-electric conversion efficiency (g) and energy storage capacity via introducing composited ZnO/polyvinylidene fluoride (PVDF) nanostructure in CE.…”
mentioning
confidence: 99%
See 1 more Smart Citation